2020
DOI: 10.3390/ph13090262
|View full text |Cite
|
Sign up to set email alerts
|

Fragaria viridis Fruit Metabolites: Variation of LC-MS Profile and Antioxidant Potential during Ripening and Storage

Abstract: Fragaria viridis Weston or creamy strawberry is one of the less-known species of the Fragaria genus (Rosaceae family) with a wide distribution in Eurasia and is still in the shadow of more popular relatives F. ananassa (garden strawberry) or F. vesca (wild strawberry). Importantly, there is a lack of scientific knowledge on F. viridis compounds, their stability in the postharvest period, and bioactivity. In this study, metabolites of F. viridis fruits in three ripening stages were characterized with high-perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 71 publications
2
13
0
1
Order By: Relevance
“…The changes of low-molecular-weight phenolics before and after the fermentation of E. angustifolium leaves were precisely analysed by high-performance liquid chromatography with photodiode array detection and electrospray ionization triple quadrupole mass spectrometric detection (HPLC-PDA–ESI-tQ-MS). Finally, 59 compounds were identified after comparison of their chromatographic behaviour, ultraviolet, and mass spectra with reference substances (28 compounds) and literature data [ 27 , 28 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] ( Figure 2 , Table 2 ). Only 23 of the compounds had been found in E. angustifolium previously [ 43 , 45 , 54 ]; 36 compounds were detected for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes of low-molecular-weight phenolics before and after the fermentation of E. angustifolium leaves were precisely analysed by high-performance liquid chromatography with photodiode array detection and electrospray ionization triple quadrupole mass spectrometric detection (HPLC-PDA–ESI-tQ-MS). Finally, 59 compounds were identified after comparison of their chromatographic behaviour, ultraviolet, and mass spectra with reference substances (28 compounds) and literature data [ 27 , 28 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] ( Figure 2 , Table 2 ). Only 23 of the compounds had been found in E. angustifolium previously [ 43 , 45 , 54 ]; 36 compounds were detected for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant potential of E. angustifolium melanoidin, oenothein B and trolox was studied using the known in vitro microplate spectrophotometric assays: scavenging activity against 2,2-diphenyl-1-picrylhydrazyl radicals (DPPH • ) [ 24 ], 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) cation radicals (ABTS • + ) [ 25 ], N , N -dimethyl- p -phenylenediamine radicals (DMPD •+ ) [ 26 ], superoxide anion radicals (O 2 • − ) [ 27 ], hydroxyl radicals ( • OH) [ 27 ], and chloride radicals (Cl • ) [ 28 ]. The nitric oxide (II) scavenging potential was studied in a spectrophotometric assay with sodium nitroprusside as a source of NO [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In R. matsumuranus leaves, 21 compounds were determined to be flavonols in glycoside form. By comparing their mass spectral data with those reported previously [25][26][27][28][29] and with reference standards, these flavonols were identified as derivatives of quercetin (12 compounds) and kaempferol (9 compounds). The quercetin group of flavonols was the largest with non-acylated and acylated fragments linked with carbohydrate fragments.…”
Section: Flavonolsmentioning
confidence: 87%
“…Another ellagitannin of the hexahydroxydiphenoylgalloyl-glucose type, potentillin (22), was detected previously in R. arcticus leaves [48] and R. idaeus shoots [38]. Okuda et al [47] suggested using the compounds sanguiin H6 (29) and sanguiim H11 (33) as chemotaxonomic markers of the genus Rubus. This statement applies to the considered plant object.…”
Section: Flavonolsmentioning
confidence: 96%